Peran Seni Hadroh Sebagai Media Dakwah Pada Majelis Ikatan Remaja Masjid Fisabilillah Kota Palembang - Iogi Al Hikmah; Hidayat HT; Emi Puspita Dewi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research discusses the role of hadroh art as a medium of da’wah at the Youth Association of Fisabilillah Mosque in Palembang City. The background of this study is based on the importance of developing creative and relevant da’wah media for the younger generation amidst the flow of modernization and popular culture that may influence Islamic values among youth. This study applies the theory of da’wah media roles proposed by Siti Muawanah, which includes informative, educative, persuasive, and guidance and control roles. The research employed a descriptive qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation involving informants consisting of the mosque youth advisor, administrators, and members of the Youth Association of Fisabilillah Mosque in Palembang City. The findings reveal that hadroh art plays an effective role as a medium of da’wah. Informatively, hadroh conveys Islamic messages through shalawat lyrics; educationally, it fosters religious understanding and moral values among youth; persuasively, it attracts young people to participate actively in mosque activities; and it also functions in guiding and directing youth toward religious behavior and love for Prophet Muhammad SAW. Therefore, hadroh art can be concluded as an effective medium of da’wah in the spiritual and social development of mosque youth.